PENGARUH MEDIA PEMBELAJARAN ROTAR GADANG TERHADAP KEMAMPUAN BERPIKIR KRITIS PADA SISWA KELAS IV UPT SPF SDN 106168 DELI TUA T.A 2024/2025 - Harahap, Siti Zahara; Simbolon, Rinci; Sembiring, Bella Nadia; Simatupang, Ernita (Jurnal Curere, 2025)
This research aims to analyze the effect of using Rotar Gadang learning media on the critical thinking abilities of class IV students at UPT SPF SDN 106168 Deli Tua. The research method used was quantitative with a pre-experimental design, one group pre-test and post-test. The research subjects consisted of 29 students. Data collection was carried out through critical thinking ability tests before and after using learning media. The research results showed a significant increase in students' critical thinking abilities.